Medicinal plants used in Peru for the treatment of respiratory disorders - Bussmann, Rainer W. (2010)
Respiratory tract infections continue to be a major health challenge worldwide especially due to the increasingly fast development of resistance to the drugs currently in use. Many plant species are traditionally used for respiratory illness treatment, and some have been investigated for their efficacy with positive results. A total of 91 plant species belonging to 82 genera and 48 families were documented and identified as respiratory system herbal remedies in Northern Peru. Most species used were Asteraceae (15 species, 16.67%), followed by Lamiaceae and Fabaceae (8.89% and 5.56%). The majority of respiratory disorder herbal preparations were prepared from the leaves of plants (27.69%), while the whole plant (18.46%), flowers (13.85%) and stems (17.69%) were used less frequently. In almost 55% of the cases fresh plant material was used to prepare remedies. About 86% of the remedies were applied orally, while the remaining ones were applied topically. Over half of all remedies were prepared as mixtures of multiple ingredients. Almost 50% of the plants found in the respiratory pharmacopoeia of Northern Peru, or their congeners have been studied for their medicinal properties. The results of this study show that both indigenous and introduced species are used for the treatment of respiratory system disorders. The information gained on frequently used traditional remedies might give some leads for future targets for further analysis in order to develop new drugs.